PENGARUH EMOTIONAL QUOTIENT DAN MOTIVASI BELAJAR TERHADAP DAYA JUANG MAHASISWA JURUSAN PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG DALAM RANGKA MENYELESAIKAN STUDI - Feni Fatmawati; Agus Irianto; Dessi Susanti (Universitas Negeri Padang, 2018)
The purpose of this study is to determine the effect of emotional quotient and learning motivation to the adversity quotient of students of the Department of Economic Education Faculty of Economics, State University of Padang in order to complete the study. This study is a descriptive quantitative research. The population of this study are Students of Economic Education Department of Faculty of Economics of State University of Padang 2014, 2015, 2016 and 2017 years, a namber 439 students and obtained as many samples 81 students by using a formula purposive sampling. The data used are primary data obtained through the distribution of questionnaires to the students of the Department of Economic Education Faculty of Economics, State University of Padang 2014, 2015, 2016 and 2017 years. The analytical method used is descriptive and quantitative with multiple regression analysis using SPSS version 16. The results showed that: (1) Emotional quotient significantly affects the student's desire of the Department of Economic Education Faculty of Economics, State University of Padang in order to complete the study (2) The motivation to learn not significantly influence the students' desire of the Department of Economic Education, Faculty of Economics, State University of Padang in order to complete the study. Keyword : Emotional Quotient, Learning Motivation, and Adversity Quotient